Les Dominicains au Portugal du xiiie à la fin du xve siècle. Éléments de synthèse sur leur histoire et leur architecture - Saul António Gomes; Jean-Marie Guillouët (Mélanges de la Casa de Velázquez)
The paper firstly proposes an overview of the research on the history of the presence of the Order of St. Dominic in medieval Portugal, highlighting the historical context of the arrival of the first friars, around 1215-1220, the social conditions of the foundations and the support networks. This historical framework, which highlights the close link between the Order and the monarchical power, is necessary to understand the context of the construction of the convents, the strategies of implantation and the architectural choices, in a territory caught in a dialectic between an artistic isolation resulting from geographical marginalisation and the extraordinary permeability of the craftsmen and the patrons to foreign influences. The study of the architectural characteristics of the Portuguese Dominican convents, proposed in a second phase, focuses on the case of Santa Maria da Vitória de Batalha, founded by King João I at the end of the 14th century. Santa Maria da Vitória is an outstanding monument, due to its close link with the new Portuguese royal dynasty. Its architecture is complex and reveals a phenomenon of updating of the constructive forms, whereas, at the same time, formulas that had been practiced for more than one and a half centuries were maintained.